2008
DOI: 10.2460/ajvr.69.10.1286
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory spatial data analysis of regional seroprevalence of antibodies against epizootic hemorrhagic disease virus in cattle from Illinois and Indiana

Abstract: Seroprevalence of antibodies against EHDV in cattle was higher in the south than north; however, local complexities existed that were not observed in a serosurvey of antibodies against bluetongue virus from the same cattle population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
(14 reference statements)
2
9
0
Order By: Relevance
“…Additional test results from cattle in Illinois (2000-02) support these results with a low reported prevalence (1-2%) of BTV antibodies (Boyer et al 2007). Consistent with our virus isolation results, Boyer et al (2008) reported that prevalence of EHDV antibodies in these same 2000-02 cattle sera ranged from 5% to 15%. The apparent variation in the prevalence of EHDV and BTV may relate to differences in the distribution of Culicoides vectors associated with these viruses.…”
Section: Discussionsupporting
confidence: 87%
“…Additional test results from cattle in Illinois (2000-02) support these results with a low reported prevalence (1-2%) of BTV antibodies (Boyer et al 2007). Consistent with our virus isolation results, Boyer et al (2008) reported that prevalence of EHDV antibodies in these same 2000-02 cattle sera ranged from 5% to 15%. The apparent variation in the prevalence of EHDV and BTV may relate to differences in the distribution of Culicoides vectors associated with these viruses.…”
Section: Discussionsupporting
confidence: 87%
“…In Montana, a low prevalence of BTV antibodies ( < 2.0%) has been reported in cattle (Van Donkersgoed et al 2001, 2006. Similar results have been reported in cattle in northern Indiana and Illinois (Boyer et al 2008) and in North Dakota and South Dakota (Green et al 2005); in these states, antibody prevalence decreased with increasing latitude. Occasional outbreaks have occurred historically along the northern edge of the BTV distribution in the United States as early as 1966 near Billings, MT ( Jones and Leudke 1969).…”
Section: Introductionsupporting
confidence: 79%
“…The risk maps produced by these models do provide insight into the distributions of BTV and EHDV that is not apparent when regression results are presented in a table or when prevalence is aggregated by state or zone. 22,23 The pattern of EHDV seropositivity is suggestive of potential sites where Culicoides sampling could be targeted. Furthermore, the locations of outliers provide clues about where climatic and landscape variables fail to adequately explain the variation in BTV and EHDV seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Briefly, blood samples were obtained from the cattle after three transmission seasons (2000,2001,2002). Sixty herds participated in the study during at least one of the years, 52 in Illinois and 8 in western Indiana.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation